Ontogeny of Tumor-Associated Macrophages - Laviron, Marie; Boissonnas, Alexandre (Frontiers in Immunology, 2019)
Tumor-associated macrophages (TAM) represent the main immune cell population of the tumor microenvironment in most cancer. For decades, TAM have been the focus of intense investigation to understand how they modulate the tumor microenvironment and their implication in therapy failure. One consensus is that TAM are considered to exclusively originate from circulating monocyte precursors released from the bone marrow, fitting the original dogma of tissue-resident macrophage ontogeny. A second consensus proposed that TAM harbor either a classically activated M1 or alternatively activated M2 polarization profile, with almost opposite anti- and pro-tumoral activity respectively. These fundamental pillars are now revised in face of the latest discoveries on macrophage biology. Embryonic-derived macrophages were recently characterized as major contributors to the pool of tissue-resident macrophages in many tissues. Their turnover with macrophages derived from precursors of adult hematopoiesis seems to follow a regulation at the subtissular level. This has shed light on an ever more complex macrophage diversity in the tumor microenvironment than once thought and raise the question of their respective implication in tumor development compared to classical monocyte-derived macrophages. These recent advances highlight that TAM have actually not fully revealed their usefulness and deserve to be reconsidered. Understanding the link between TAM ontogeny and their various functions in tumor growth and interaction with the immune system represents one of the future challenges for cancer therapy.